1986
DOI: 10.1007/bf00981141
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of oxaprozin with acetaminophen, cimetidine, and ranitidine

Abstract: Twelve healthy male volunteers participated in a single-dose four-way crossover study to evaluate potential drug interactions with oxaprozin, a nonsteroidal antiinflammatory agent of the propionic class. The four modes of administration were: a. oxaprozin, 1200 mg alone; b. oxaprozin during concurrent acetaminophen, 500 mg 4 times daily; c. oxaprozin with cimetidine, 300 mg 4 times daily; d. oxaprozin with ranitidine, 150 mg every 12 hours. Acetaminophen, cimetidine, or ranitidine were begun 24 hours prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…In 1 study with oxaprozin, only the oral clearance was found to be decreased (-20%), following a 10-day ranitidine treatment (Scavone et al 1986). The clinical consequences are unknown, but undoubtedly very limited due to the wide therapeutic margin of oxaprozin.…”
Section: Other Analgesicsmentioning
confidence: 95%
“…In 1 study with oxaprozin, only the oral clearance was found to be decreased (-20%), following a 10-day ranitidine treatment (Scavone et al 1986). The clinical consequences are unknown, but undoubtedly very limited due to the wide therapeutic margin of oxaprozin.…”
Section: Other Analgesicsmentioning
confidence: 95%
“…Aspirin je pokazao interakciju sa oksaprozinom vezanim za albumin [50]. Nisu utvrđene klinički značajne intrakcije oksaprozina prilikom istovremene primene sa antagonistima H 2 receptora, antacidima ili paracetamolom [51,52].…”
Section: Farmakokinetika Oksaprozinaunclassified